Strong D* → Dπ and B* → Bπ couplings - El-Bennich, Bruno [UNESP]; Ivanov, Mikhail A.; Roberts, Craig D. (American Physical Society (APS), 2011)
We compute gD*Dπ and gB*Bπ using a framework in which all elements are constrained by Dyson-Schwinger equation studies of QCD and therefore incorporates a consistent, direct, and simultaneous description of light and heavy quarks and the states they may constitute. We link these couplings with the heavy-light-meson leptonic decay constants and thereby obtain gD*Dπ=15.9-1.0+2.1 and g B*Bπ=30.0-1.4+3.2. From the latter, we infer ǧB=0.37-0.02+0.04. A comparison between g D*Dπ and gB*Bπ indicates that when the c quark is a system's heaviest constituent, ΛQCD/m c-corrections are not under good control. © 2011 American Physical Society.